Harry the clever spider - Jarman, Julia; Fowkes, Charlie, illus (London : Collins, 2005)
Clare found Harry, a big hairy spider, and wanted to keep him. Mum, Dad and Charlie had other ideas. It was up to Harry to make them change their minds.
Turquoise Band 7.
Keywords: Friendship -- Fiction; Human -- Animals friendship; Spiders -- Fiction